QAṢAṢ QUR’ĀNI DALAM TAFSIR AL-BAQARAH KH ZAINI MUN’IM: “TELAAH KISAH PENCIPTAAN NABI ADAM SEBAGAI KHALĪFAH” - Khoirul Anas (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2020)
Abstract: This research explains as well as examines KH Zaini Mun'im's thoughts about Qiṣas Qur'aniyyah, and the purpose of this research is to find out how KH Zaini Mun'im's concept of thinking about Qiṣas Quraniyyah issues. The method used in writing this research is library (library resarch). Meanwhile, the data collection was carried out using literature review techniques using the work of KH Zaini Mun'im's interpretation as primary data and literature related to the title of this research study (such as books, journals, etc.) as secondary data. Then the data collected is analyzed using content analysis to analyze the contents according to the needs, so that a conclusion can be drawn. The results of the research show that: 1) the method used by KH Zaini Mun'im in assessing Qiṣas Quraniyyah is in accordance with the classification of the Qiṣas Quraniyyah study method proposed by Sheikh Mahmud Syaltut, namely the moderate method, looking at the substances summarized in this method that KH has tried to apply. Zaini Mun'im, like respecting the editorial staff of a verse and focusing on language studies in studying stories. 2) KH Zaini Mun'im's thought about the story of Adam's creation is more inclined to the thought of the ulama 'salaf who say that the story told by the Al-Qur'an is true even though the story cannot be proven logically.